Determinants of exercise adherence and maintenance for cancer survivors: Implementation of a community-based group exercise program. A qualitative feasibility study - Maria Ranes; Tor Helge Wiestad; Inger Thormodsen; Cecilia Arving (Elsevier, 2022)
Objective: Despite verified knowledge that physical exercise plays an important part in recovery after cancer treatment, multiple studies have shown that maintaining a physically active lifestyle after cancer is challenging. There is a need for qualitative studies to increase understanding into patient experiences and perspectives, and facilitate the design of more sustainable exercise program. This qualitative descriptive feasibility study explores experiences from the implementation of a novel four-month community-based group exercise program for cancer survivors within municipality health service after completion of rehabilitation in the specialist health care service. Methods: Fourteen cancer survivors participated in focus group interviews after completing Rehabilitation: Physical activity and Coping - feasibility study. Data were analyzed using the systematic text condensation method. Results: We identified a main category, Determinants for exercise adherence and maintenance and four subcategories: peer-support, environment, structure and knowledge. Conclusion: A social and supportive exercise environment promotes exercise adherence and maintenance among cancer survivors. This knowledge can be useful for further efforts to implement high quality community-based group exercise programs for cancer survivors. Innovation: This study adds knowledge of survivors' experience of a novel community-based group exercise program in clinical practice and can promote the implementation of sustainable community-based exercise programs for cancer survivors.